Karakteristik Individu dan Kebijakan Anti-Merokok pada Perokok Berat di Indonesia - Vebby Amelia Edwin; Welly Welly; Riyana Husna; Rahimatul Uthia (Universitas Sumatera Barat, 2025)
Hardcore smokers represent a critical subgroup in the tobacco epidemic due to their high nicotine dependence and low motivation to quit, making them difficult to reach through conventional cessation strategies. This study aims to analyze the association between individual characteristics and anti-smoking policies with hardcore smoking behavior in Indonesia. A cross-sectional design was employed using secondary data from the Global Adult Tobacco Survey (GATS) Indonesia 2021. A total of 2,837 current smokers who met the inclusion criteria were included in the analysis. Bivariate and multivariate logistic regression were used to examine the determinants of hardcore smoking. The prevalence of hardcore smokers was 7.47%. Significant predictors of hardcore smoking included early smoking initiation before age 15 (AOR = 5.9; p < 0.001) and between ages 15–24 (AOR = 4.83; p = 0.001), employment status (AOR = 4.39; p = 0.032), poor knowledge of tobacco-related health risks (AOR = 2.51; p < 0.001), and living in households without smoke-free home policies (AOR = 2.33; p = 0.011). These findings highlight the need for integrated interventions to prevent early initiation, improve tobacco-related health literacy, and strengthen smoke-free home policies. This study provides population-based evidence to support more targeted and effective tobacco control strategies, particularly for high-risk groups.